Determinan Kejadian Stunting pada Balita Usia 24-59 Bulan di Wilayah Kerja Puskesmas Pahandut Kota Palangka Raya: Determinants of Stunting Events in Tolls Aged 24-59 Months in the Work Area of Pahandut Puskesmas City, Palangka Raya - Erina Eka Hatini; Intan Mustika Sari; Greiny Arisani (Jurnal Surya Medika (JSM), 2023)
Stunting is a condition of growth failure in children (body and brain) due to lack of nutritional intake so that it can cause growth disorders in children who have less height compared to age. Maternal health and nutrition conditions during pregnancy and during pregnancy and after delivery can affect fetal growth and can lead to the risk of stunting. Based on WHO, the Z-score for height for age less than -2 standard deviations (<-2 SD) is categorized as stunting. Stunting is a linear growth disorder that can affect the increased risk of illness, death, delayed motor development disorders, and stunted mental growth. This study aims to determine the factors associated with the incidence of stunting at the Pahandut Public Health Center, Palangka Raya. This study used an observational method with a cross sectional research design. The sample in this study were 96 toddlers who were in the work area of the Pahandut Health Center. Data were analyzed by univariate and bivariate by using chi-square test. The results showed that the factors associated with stunting were a history of exclusive breastfeeding with a p-value of 0.031, a history of infectious diseases with a p-value of 0.041. Based on the results obtained, it can be concluded that the factors that have a significant relationship with the incidence of stunting in the work area of the Pahandut Health Center, Palangka Raya City are the history of exclusive breastfeeding and a history of infectious diseases.